A HISTORY OF IDEAS IN SCIENCE EDUCATION : IMPLICATIONS FOR PRACTICE - DeBoer, George E., author 654893 (New York : Teachers College Press, 2009)
By allowing key scientists, researchers, professors, and classroom teachers of science to speak for themselves through their published writings about what is best and needed for the field, Dr. DeBoer presents a fascinating account of the history of science education in the United States from the middle of the 19th century to the present. The book relates how science first struggled to find a place in the school curriculum and recounts the many debates over the years about what that curriculum should be. In fact, many of what we consider modern ideas in science education are not new at all but can be traced to writings on education of one hundred years ago. The book is aimed at all those interested in science education: classroom teachers and science education leaders concerned about the historical justification of the goals and strategies proposed for the field. The book should be enjoyed not only by the researcher but also by anyone curious about just how curriculum is decided upon and implemented on a national scale.